Handbook of crystal growth - Nishinaga, Tatau (Elsevier, 2015)
Volume IA Handbook of Crystal Growth, 2nd Edition (Fundamentals: Thermodynamics and Kinetics) Volume IA addresses the present status of crystal growth science, and provides scientific tools for the following volumes: Volume II (Bulk Crystal Growth) and III (Thin Film Growth and Epitaxy). Volume IA highlights thermodynamics and kinetics. After historical introduction of the crystal growth, phase equilibria, defect thermodynamics, stoichiometry, and shape of crystal and structure of melt are described. Then, the most fundamental and basic aspects of crystal growth are presented, along with the.- Resumé vydavatel
Keywords: růst krystalů; crystal growth; elektronické knihy; sborníky; příručky; electronic books; papers of several authors; handbooks and manuals